Technological knowledge with mathematics in the production of interactive videos (Revista BOEM, 2024)
This research highlighted the potential results obtained from the use of interactive videos in the first period of a subject in the in-person Mathematics course at a public university. As these classes were applied in times of pandemic, the modality was developed remotely through the virtual environment Microsoft Teams. As methodological procedures, we observed participants on the learning platform, with the aim of preparing university students for a modern and dynamic approach, through facilitating tools for making interactive videos. The participation of graduates resulted in the production of videos where it was possible to analyze the challenges faced, among other records. All data produced was systematized, which made it possible to highlight the importance of Technological Content Knowledge.
Keywords: interactive videos; mathematics education; digital technologies; didactic guidance